Portuguese experience in ASR aggregate assessment - Santos Silva, A. (2017)
Although considerable efforts have been made worldwide regarding alkali-silica reaction (ASR) prevention and mitigation, including the approval of new national and international regulations, several concrete structures are still being diagnosed with ASR. In Portugal, the new cases of ASR pertain to concrete produced mainly with igneous aggregates, whose potential reactivity is difficult to assess, notably on granitic and basaltic rocks. The most effective way to prevent ASR is an adequate knowledge of the alkali reactivity of the aggregate, which requires the application of appropriate tests and criteria to enable a correct classification. In the last 4 years a research program conducted in Portugal has evaluated more than 90 aggregates of different mineralogy and/or texture. The test campaign included petrography, ASTM C1260, RILEM AAR-3 and RILEM AAR-4.1 test methods. In this paper the results of ASR reactivity evaluation obtained in a group of granitic and basaltic aggregates are presented and discussed. From the results obtained, proposals to improve the reliability of existing test-methods are presented.